2006
DOI: 10.1002/anie.200504566
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphine‐Stabilized Gold–Arsenic Clusters [Au19(AsnPr)8(dppe)6]Cl3, [Au10(AsnPr)4(dppe)4]Cl2, [Au17(AsnPr)6(As2nPr2)(dppm)6]Cl3, and [Au10(AsPh)4(dppe)4]Cl2: Synthesis, Characterization, and DFT Calculations

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 66 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…179 Au 38 clusters with phosphine or thiolate ligands were calculated to develop molecular gold-thiolate rings on their surface. 180 Various, open-structured, phosphine-stabilized gold-arsenic clusters were synthesized and theoretically modelled by Sevillano et al 181 For earlier work on Au 28 (SMe) 16 and Au 38 (SMe) 24 , including their chirality aspects, recall Garzo´n et al 182 The corresponding optical activity had earlier been seen in glutathione-passsivated gold nanoclusters in the 20-40 gold atom range.…”
Section: àmentioning
confidence: 99%
“…179 Au 38 clusters with phosphine or thiolate ligands were calculated to develop molecular gold-thiolate rings on their surface. 180 Various, open-structured, phosphine-stabilized gold-arsenic clusters were synthesized and theoretically modelled by Sevillano et al 181 For earlier work on Au 28 (SMe) 16 and Au 38 (SMe) 24 , including their chirality aspects, recall Garzo´n et al 182 The corresponding optical activity had earlier been seen in glutathione-passsivated gold nanoclusters in the 20-40 gold atom range.…”
Section: àmentioning
confidence: 99%
“…For instance, Fackler et al and Fenske et al recently reported the structural characterization and luminescence of molecules with arsenic or phosphorus donor ligands containing between nine and nineteen gold centers [50][51][52]. However, in selected examples where the ligands had several donor centers, or when these could act as donors to more than one gold center, the molecules displayed a larger number of gold atoms and, usually, the aggregation occurred inside the molecules.…”
Section: Network From Higher Nuclearity Systemsmentioning
confidence: 99%
“…Mass spectrometric techniques have been proven to be very useful for elucidation of atomic compositions of large inorganic cluster molecules such as [Ag 26 In 18 S 36 Cl 6 (dppm) 10 (thf ) 4 ] 2+22 and [Au 19 (As n Pr) 8 (dppe) 6 ] 3+ . 24 The ESI-TOF mass spectra of DMF solutions of 2 in negative-ion mode are shown in Fig. 3 and are dominated by one peak of the singly charged cluster anion [Cu 19 S 28 (SnPh) 12 ] − at m/z 4454.17 (Table 3).…”
Section: Mass Spectrometrymentioning
confidence: 99%